Adaptive simulations of detonation propagation in 90-degree bent tubes. (26th October 2016) - Yuan, Xueqiang; Zhou, Jin; Lin, Zhiyong; Cai, Xiaodong
Abstract: The open-code adaptive mesh refinement program AMROC was adopted to conduct numerical simulations of detonation propagation in 90° bent tubes. Propagation modes in bent tubes, the mechanism of detonation restored to stable propagation and effects of curvature radius on detonation restoration were explored in depth. Results indicate that with the increase of initial pressure and inner wall curvature radius, detonation propagation undergoes a transition from the unstable mode to the transition mode, and finally the stable mode. The critical conditions for mode transition among the unstable mode, the transition mode and the stable mode are r 0 / λ  = 13.7 and r 0 / λ  = 22.3, respectively, where λ is the cellular width. In the unstable and transition modes, when the detonation crosses through the bent section, the detonation structure is destroyed. However, the generated Mach reflection can induce the formation of new transverse waves to realize re-initiation and the collision between two triple points can enhance the strength of the detonation gradually, which can cooperatively promote detonation restoration to self-sustained propagation. The curvature radius not only has an influence on the formation of the transverse wave, but also makes an impact on the position where the triple point of Mach reflection collides on the outer wall. The colliding position has an effect on collisions among triple points, which can influence detonation restoration eventually. Highlights: Three detonation propagation modes in bent tubes and the critical condition for mode transition are found. Transverse wave formation and collision between triple points cooperatively promote the detonation restoration. The increase of curvature radius accelerates transverse wave formation and change colliding positions on the outer wall. The colliding position in the straight outlet section is beneficial for restoration.